Sikap pelajar terhadap online learning :|bsatu kajian kes di UNIMAS - Teng, Caroline Wee Ling. (Universiti Malaysia Sarawak (UNIMAS), 2002)
The purpose ofthis study was to determine the attitude ofstudents towards online learning as a supplementary tool to traditional learning in University Malaysia Sarawak. The dependent variable In this study was students' attitude while the independent variables were gender, motivation, computer knowledge and learning environment A survey methodology and an instrument of questionaire in a form of Likert Scale were use to obtain data and from a sample of 120 respondents from an overall population of 1172 third year students from 9 faculties in Unimas. The data collected was analysed using descriptive statistics and inferential non-parametric statistics. Percentages were used to determine the distribution of gender while categories ofstudents , attitude were measured through score. Mann-Whitney U was used to determine the significant difference between males and females In terms oftheir attitude (z = -1.028, P > 0.05 ), while as the Pearson Correlation r was used to find out the significant relationship between factors of motivaiion ( r = 0.445, P < 0.05 ), computer knowledge (r = 0.348, p < 0.05) and learning environment ( r= 0.10, p > 0.05) and students' attitude towards online learning. The jlndings ofthis study showed that there was signifICant relationship between factors of motivation and computer knowledge with students' attitude towards online learning. Overall jlnding showed that students had a positive attitude towards online learning as a supplementary tool to traditional learning. The fmdlng ofthis study can help the management and lecturers of Unlmas in understanding how to create an effective motivation and improve computer knowledge in the process of teaching and learning from time to time, in order to deveiop a positive attitude towards online learning.